Robust fault estimation and fault tolerant control for three-motor web-winding systems. Issue 11 (2nd November 2021) - Chu, Xiaoyan; Nian, Xiaohong; Xiong, Hongyun; Wang, Haibo
Abstract : This paper studies the problems of fault estimation and fault tolerant control for three-motor web-winding systems in the presence of multiple disturbances and actuator faults. A disturbance compensation-based fault estimation observer is designed to estimate the system actuator faults. By setting the reference outputs, a method of obtaining equilibrium control inputs and equilibrium states is formulated to achieve the variation dynamic model at equilibrium points by Taylor expansion. Then, based on the estimated actuator faults, an effective fault tolerant control strategy is proposed by the methods of interval matrix and disturbance local compensation. Sufficient conditions of asymptotic stability of the estimation error system and the closed-loop system are derived based on the Lyapunov theory. Fault estimation observer and fault tolerant controller gain matrices are obtained by solving the linear matrix inequalities. Finally, simulations and analysis are performed to verify the effectiveness of the proposed method.